2010
DOI: 10.1111/j.1442-200x.2009.02942.x
|View full text |Cite
|
Sign up to set email alerts
|

Early postpartum discharge and breastfeeding: An observational study from France

Abstract: Early postpartum hospital discharge organized by skilled professionals is compatible with a satisfactory rate of exclusive breastfeeding up to the return to work. Formalized programs of instruction for perinatal professionals would help to reduce early abandonment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
2
15
0
2
Order By: Relevance
“…Mother's decision to breastfeed already during pregnancy has a bearing on how long she actually breastfeeds (Kim et al 2013). Even the support she gets in case of uprising problems has an impact (Cambonie et al 2010). In a British study mothers' reported reasons why they started to give their infant solid foods before recommendation was that they believed the infant to be hungry or that they had concerns regarding infant weight.…”
Section: Introductionmentioning
confidence: 99%
“…Mother's decision to breastfeed already during pregnancy has a bearing on how long she actually breastfeeds (Kim et al 2013). Even the support she gets in case of uprising problems has an impact (Cambonie et al 2010). In a British study mothers' reported reasons why they started to give their infant solid foods before recommendation was that they believed the infant to be hungry or that they had concerns regarding infant weight.…”
Section: Introductionmentioning
confidence: 99%
“…A positive and supportive attitude from the staff at the maternity ward is known to create a sense of security for the parents. On the contrary, a number of studies [24][25][26] show that breastfeeding is not significantly affected by early hospital discharge. However, other studies [23,[27][28] highlight that the need for professional support was extensive during the first few days at home, regardless of early hospital discharge or longer stay at the maternity ward.…”
Section: Discussionmentioning
confidence: 92%
“…Further, a larger gap of EBF rate was found between our study and several studies overseas. The EBF rate at hospital discharge was 49.9% in Riverside County of USA [36] , 76.8% in Italy [37] ,77.8% in France [38] and 82.7% in regional Western Australia [39] . The EBF at the hospital discharge in Shanghai was far below the recommendation of BFHs, which required 80% of newborns being exclusively breastfed [40] .…”
Section: Discussionmentioning
confidence: 97%